2021
DOI: 10.1029/2021gc009657
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Fractionation in Noelaerhabdaceae Algae in Culture and a Critical Evaluation of the Alkenone Paleobarometer

Abstract: Anthropogenic CO 2 emissions are perturbing the global carbon cycle more rapidly than at any time in the last 66 million years (Zeebe et al., 2016). A key component of the natural carbon cycle is coccolithophores, which modify oceanic dissolved inorganic carbon and alkalinity inventories through photosynthetic carbon fixation and the biogenic production of calcium carbonate plates (Balch et al., 1992). These eukaryotic algae are abundant and widely distributed throughout the global oceans today (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 113 publications
(246 reference statements)
3
22
0
Order By: Relevance
“…Blanco-Ameijeiras et al (2020) measured cell membrane permeability to CO 2 in E. huxleyi and found CO 2 permeability was approximately 1e −4 m s −1 . However, here we apply an effective permeability of 2.0e −5 m s −1 so τ values used here are comparable to those reported in recent culture work (Phelps et al, 2021).…”
Section: Carbon Demand Relative To Diffusive Co 2 Supply (τ)supporting
confidence: 57%
See 4 more Smart Citations
“…Blanco-Ameijeiras et al (2020) measured cell membrane permeability to CO 2 in E. huxleyi and found CO 2 permeability was approximately 1e −4 m s −1 . However, here we apply an effective permeability of 2.0e −5 m s −1 so τ values used here are comparable to those reported in recent culture work (Phelps et al, 2021).…”
Section: Carbon Demand Relative To Diffusive Co 2 Supply (τ)supporting
confidence: 57%
“…Recent syntheses of culture data have elucidated the quantitative relationships between various physiological and environmental influences, and confirmed that ε p does indeed decline as [CO 2(aq) ] decreases (e.g., Phelps et al, 2021;Stoll et al, 2019). However, culture experiments suggest that light energy, independent of its effect on growth rate, is nearly as important a control on ε p as physiology and CO 2 , with higher ε p occurring at higher irradiance (Phelps et al, 2021;Stoll et al, 2019;Wilkes & Pearson, 2019). Though alkenone ε p (ε p37:2 , subscript representing the diunsaturated ketone with 37 carbon atoms) has been extensively used to generate paleo-CO 2 records, only two studies have quantitatively considered cell size, growth rate, and irradiance when interpreting alkenone ε p in down-core sediment sequences (Stoll et al, 2019;Tanner et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations